IMPLEMENTASI FILTER DIGITAL IIR BUTTERWORTH PADA DSP STARTER KIT TMS320C3x - Winarsih, Irda; Agoes, Suhartati; Wahyudi, Robert (Jurnal Teknik Elektro, 2003)
This article converses TMS320C3x DSP Starter Kit (DSK) board utilization as Butterworthinfinite impulse response (IIR) digital filter. Specification parameters of the filter can bechanged as long as they do not exceed performance limits of the DSK board.The resulted Butterworth filter performance is compared to the theoretical one obtainedusing Matlab signal processing toolbox. Test result shows that performance of theimplemented filter is similar with its theoretical model.Keywords: Butterworth, TMS320C3x DSK, infinite impulse response, digital filter